The adoption of e-learning 2.0 in higher education by teachers and students: An investigation using mixed methods approach - Zakaria, Mohd Hafiz; Watson, Jason; Edwards, Sylvia L. (2011)
This paper describes an approach to investigate the adoption of Web 2.0 in the classroom using a mixed methods study. By using a combination of qualitative or quantitative data collection and analysis techniques, we attempt to synergize the results and provide a more valid understanding of Web 2.0 adoption for learning by both teachers and students. This approach is expected to yield a better holistic view on the adoption issues associated with the e-learning 2.0 concept in current higher education as opposed to single method studies done previously. This paper also presents some early findings of e-learning 2.0 adoption using this research method.